Nurses’ Self-Assessment Of Caring Behaviors In Nurse-Patient Interactions - Alosaimi, Meshari Hameed Hamed; Alzahrani, Mosa Rashed Abdullah; Alqahtani, Hayyaf Mohammed; Aloseimy, Sultan Meqaed Shleweeh; Alqahtani, Hamad Saod Fahad; Al-Harbi, Salman Hamoud Ali; Mohamed, Hamda; Essa Saqer Alotaibi; Qasem Marzouq Alotaibi; Mishal Sanhat Al-Sahli (Migration Letters, 2023)
Background: Nursing practice is centered on caring and nurses’ behavior has an impact on the quality of patient care and it is predictive of patient satisfaction, however, many nurses, in reality, do not exhibit caring behavior when providing nursing care to patients. Nurse-patient interactions based on caring behaviors ensure better working conditions and better-quality healthcare. The aim of this study is to examine how nurses self-assess the frequency of applying caring behaviors in nurse–patient interactions and to identify the differences in the application frequency of caring behaviors in relation to work experience and education level. Methods: A cross-sectional study was conducted in different clinical departments of the Hospital in Riyadh, KSA from January to April 2023. The respondents were Bachelor of Science (BSc) nurses and nurses. The [1]survey used the "Caring Nurse–Patient Interactions Scale (Nurse Version)". The respondents assessed the caring behaviors from the subscale "needs" as the most frequently applied (median (Me): 4.7; interquartile range (IQR): 4.4–4.9), while the least frequently applied were the procedures from the subscale "sensitivity" (Me: 3.8; IQR: 3.2–4.3). Results: The nurses reported applying caring behaviors to the subscales "hope" (p < 0.001), "problem-solving" (p = 0.003), and "environment" (p = 0.021) more frequently than BSc nurses did. Compared with less experienced respondents, the respondents with more than 30 years of work experience applied the caring behaviors on the subscales "sensitivity" (p = 0.009), "expression of emotions" (p = 0.001), "problem-solving" (p = 0.008), and especially "humanism" and "spirituality" (p < 0.001) more frequently. Conclusion: The results indicate that respondents are more focused on applying skills or carrying out a task than on caring behaviors which is about demonstrating compassion, loving kindness, and relationships.